The Input of a Successful EFL Learner and the Mastery of Gen-Z Slangs - Endar Rachmawaty Linuwih; Gabriella Kristina Handayani (Institut Agama Islam Negeri Palopo, 2022)
Language changes and one of the concrete poofs is the existence of new slang words. Slang is an informal language that is widely used by a teenager. Slang words differ for each country; therefore, this study aims to know the input of a successful English learner from Indonesia and the knowledge of Gen Z's English slang. The research was conducted using qualitative data analysis as the method design in order to get a deeper understanding of the respondent and research topic. The result shows that the respondent was exposed to both formal and informal input. Out of 25 questions given about slang words, the respondent was able to define three slang words correctly. The possible reasons why the respondent did not do well in the slang words test are because (1) the English education in Indonesia does not focus on teaching slang words, (2) the people the respondent follows on social media are not from gen z, (3) the respondent does not spend much time on social media, or the topics/ contents are not using general slang words, (4) the sources of input of the respondent were not published recently, (5) offline game cannot connect people worldwide, (6) the respondent might have heard or read one or two slang words but did not search for its meaning. In conclusion, even though the respondent of this research was the best graduate of the English Department, the respondent did not know and follow nowadays English language very well.